Dry direct-seeded and broadcast rice: a profitable and climate-smart alternative to puddled transplanted aus rice in Bangladesh - Ahmed, Sharif; Kumar, Virender; Asad Uz Zaman; Dewan, Mahbubur Rahman; Amina Khatun; Hossain, M. Khaled; Singh, Sudhanshu; Timsina, Jagadish; Krupnik, Timothy J. (Elsevier, 2025)
Context: Dry direct-seeded rice (DSR) has been identified as a potential crop establishment method to reduce labor, water, and energy use, as well as the carbon footprint and is considered as a climate-smart practice for rice production. However, the economic feasibility and farmers’ adoption of DSR will likely depend on its productivity compared to the dominant practice of puddled transplanted rice (PTR). Tillage and crop management practices, landscape position, and rice cultivars are also likely to influence DSR productivity, profitability, energy use, and global warming potential (GWP). While numerous studies have compared the performance of DSR with PTR, none have evaluated DSR across different landscape positions to identify the most suitable landscape for expansion of DSR. Methods: We conducted multilocation and multi-year trials comparing the performance of spring ‘aus’ season rice establishment methods (machine drilled DSR, broadcasted DSR, and PTR) using three rice varieties (BRRI dhan83, BRRI dhan85, and Binadhan-19) under three landscape positions (highland, medium highland, and lowland) in three distinct districts and agroecological zones of Bangladesh. We evaluated productivity, profitability, energy use efficiency (EUE), energy productivity (EP), GWP, and yield-scaled emissions of each of these tillage and crop establishment systems. Results: Our results showed that the DSR had a similar or slightly lower yield (2–8 %) than PTR, but with lower labor use (15–47 %), lower production cost (US$ ∼150 ha−1), and higher net profit. Drill-DSR yielded similar to PTR under highlands and medium highlands, but as 9–16 % lower when grown on lowlands. EUE and EP were 15–40 % higher in DSR than in PTR due to lower energy requirements. Higher energy use in PTR primarily resulted from extra energy required for nursery raising, transplanting, puddling, and irrigation. DSR was associated with lower GWP and yield-scaled emissions of 56 to 66 % compared to PTR. Conclusions: This study suggests that DSR can be a more environmentally sound, economically viable, and climate-smart production system, found more suitable for highland and medium-highland environments. However, for the widespread adoption of DSR in Bangladesh and South Asia as a whole, the nuiances of landscape position should be considered and appropriate technological, social, and policy-level interventions will be necessary.